Initiation into the Mysteries of the Ancient World - Bremmer, Jan N. (2014)
The ancient Mysteries have long attracted the interest of scholars, an interest that goes back at least to the time of the Reformation. After a period of interest around the turn of the twentieth century, recent decades have seen an important study of Walter Burkert (1987). Yet his thematic approach makes it hard to see how the actual initiation into the Mysteries took place. To do precisely that is the aim of this book.It gives a ‘thick description’ of the major Mysteries, not only of the famous Eleusinian Mysteries, but also those located at the interface of Greece and Anatolia: the Mysteries of Samothrace, Imbros and Lemnos as well as those of the Corybants. It then proceeds to look at the Orphic-Bacchic Mysteries, which have become increasingly better understood due to the many discoveries of new texts in the recent times. Having looked at classical Greece we move on to the Roman Empire, where we study not only the lesser Mysteries, which we know especially from Pausanias, but also the new ones of Isis and Mithras. We conclude our book with a discussion of the possible influence of the Mysteries on emerging Christianity.Its detailed references and up-to-date bibliography will make this book indispensable for any scholar interested in the Mysteries and ancient religion, but also for those scholars who work on initiation or esoteric rituals, which were often inspired by the ancient Mysteries...